Heme Oxygenase-1-Modified Bone Marrow Mesenchymal Stem Cells Combined with Normothermic Machine Perfusion Repairs Bile Duct Injury in a Rat Model of DCD Liver Transplantation via Activation of Peribiliary Glands through the Wnt Pathway - Xuan Tian; Huan Cao; Longlong Wu; Weiping Zheng; Mengshu Yuan; Xiang Li; Hongli Song; Zhongyang Shen (Stem Cells International)
Livers from donors after circulatory death (DCD) are inevitably exposed to a longer warm ischemic period, which might increase the incidence of postoperative bile duct complications. Bone marrow mesenchymal stem cells (BMMSCs) have tissue repair properties. The present study was aimed at exploring the repair effect of heme oxygenase-1- (HO-1-) modified BMMSCs (HO-1/BMMSCs) combined with normothermic machine perfusion (NMP) on bile duct injury after DCD liver transplantation and at revealing the underlying mechanisms. Rat livers were exposed to in situ warm ischemia for 30 min; then, NMP was performed through the portal vein for 4 h with BMMSCs, HO-1/BMMSCs, or neither before implantation. Obvious bile duct histological damage and liver functional damage were observed postoperatively. In the group treated with HO-1/BMMSCs combined with NMP (HBP group), liver functions and bile duct histology were improved; meanwhile, cell apoptosis was reduced and cell proliferation was active. A large number of regenerative cells appeared at the injured site, and the defective bile duct epithelium was restored. Dilatation of peribiliary glands (PBGs), proliferation of PBG cells, high expression of vascular endothelial growth factor (VEGF), and increased proportion of bile duct progenitor cells with stem/progenitor cells biomarkers were observed. Blocking Wnt signaling significantly inhibited the repair effect of HO-1/BMMSCs on bile duct injury. In conclusion, HO-1/BMMSCs combined with NMP were relevant to the activation of biliary progenitor cells in PBGs which repaired bile duct injury in DCD liver transplantation via the Wnt signaling pathway. Proliferation and differentiation of PBG cells were involved in the renewal of the injured biliary epithelium.